Level of Metropolisation in Chosen Urban Centers in Poland : Meaning of Scales and Variables - Heffner, Krystian; Gibas, Piotr (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The paper deals with methodology and empirical questions of scales and variables in regional and urban economy research. There are two practical goals – statement of "metropolisation" level of urban centers on regional and sub-regional level in Poland and assessment as far metropolitan areas on regional and sub-regional level fit formal (administrative) regional division (NUTS2). Theoretic goal of the paper is to assess as far final results of spatial division to different regional units depends on the way of variables selection to be examined. There were analyzed an impact of such factors as number of variables and modification of indicators scale method (without weights, weights, with scales depended on distance to all regional and sub-regional centers, with scales depended on the distance to every regional center separately.The functional areas were demarcated on macro-regional, regional and sub-regional level on 30 indicators described 5th dimensions of "metropolisation" level. The calculation was driven on information from Local Data Bank for the year 2010 in the framework of Poland's local administrative units (predominantly).